The Effect of Simplified Kundalini Yoga (SKY) Practices on Stress and Serum Cortisol Levels Among Medical Students - Panneerselvam Periasamy; Vajiravelu Suganthi; M Ganesh Kamath; Sasikala Gunasekaran; Krishnakumar Vaithilingam; Fernando Princy (Journal of Pharmacy and Bioallied Sciences)
Background: Medical students often experience high levels of stress, which can negatively impact their mental and physical health. Elevated stress levels activate the hypothalamic–pituitary–adrenal (HPA) axis, leading to increased serum cortisol, a key biomarker of stress. Simplified Kundalini Yoga (SKY) is a holistic practice that incorporates meditation, breathing techniques, and physical exercises, which may help mitigate stress. Objective: This study aimed to evaluate the effects of SKY on perceived stress and serum cortisol levels among medical students. Methods: A quasi-experimental study was conducted among 120 first-year medical students at Government Erode Medical College. Participants were randomly assigned to either the experimental group (n = 60), who practiced SKY for 24 weeks, or the control group (n = 60), who received no intervention. Perceived Stress Scale (PSS) scores and serum cortisol levels were measured at baseline, after 12 weeks, and after 24 weeks. Repeated measures ANOVA was used for statistical analysis. Results: The experimental group exhibited a significant reduction in stress scores, decreasing from 24.47 at baseline to 14.05 after 24 weeks (F = 83.82, P < 0.001), while the control group showed no significant change (F = 0.43, P = 0.65). Similarly, serum cortisol levels in the experimental group decreased significantly from 19.90 μg/dL at baseline to 17.66 μg/dL after 24 weeks (F = 29.24, P < 0.001), whereas the control group showed no significant change (F = 1.132, P = 0.29). Conclusion: SKY effectively reduces perceived stress and serum cortisol levels among medical students, highlighting its potential as a stress-management intervention in medical education. Integrating SKY into medical curricula could enhance students’ mental well-being and resilience. Further research is needed to explore the long-term benefits and broader applications of SKY in stress management.